Media Construction of Female Legislators Figure (Framing Analysis about The Role of DPR RI Female Legislators from 2009-2014 Period in Kompas Newspaper) - Pinastika Intar Ardani; Triyono Lukmantoro, S.Sos, M.Si (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
The mass media is a weapon for the patriarchal ideology to implant into the minds of the public. Through the news that is gender bias, the media can influence public’s political attitudes to fight for women's representation in parliament. The purpose of this study is to determine how Kompas does the framing about the figure of DPR RI Female Legislators from 2009 to 2014 period. In order to achieve the goals, this research is done by using muted group theory as one variant of the theories that explains the “silencing/muting” language study through the language of the dominant group. By using constructionist paradigm, research is conducted using qualitative method and Zhongdang Pan and Gerald M. Kosicki framing analysis. The subjects of this study are the news about DPR RI female legislators 2009-2014 period from the printed version/newspaper of Kompas in 2009 and 2014. The result of this study shows that the news in Kompas contributes to the perpetuation of patriarchal ideology. The perpetuation of this ideology is shown on the news regarding the role of female legislators on domestic issues to strategic political issues. Apparently, Kompas is not only silencing/muting women through the usage of language patterns, but it is also followed by the framing of the news that prioritizes the popularity aspect of female legislators as the entertainers (name makes news) that gives rise to the